Postoperative Nosocomial Infections and Antimicrobial Resistant Pattern of Bacteria Isolated Among Patients Admitted at Ad-din Women’s Medical College Hospital, Dhaka - Akter, Mursheda; Lutfor, Afzallunessa Binte; Hassan, Munir; Chowdhury, Ferdausi; Nug, Arpita; Akter, Nayeema; Shaha, Shimu; Rahman, Musrat (Journal of Dhaka National Medical College & Hospital, 2013)
Objective: To find out the causative agents and antibiotic resistant pattern of organisms isolated from surgical site wound infection. Place of study: This study was carried out in microbiology department, Ad-din Women's Medical Collage, Moghbazar Dhaka. Method of study: The was carried out from January to December 2011 in microbiology department Ad-din women's medical college hospital. One hundred and thirty three clinically suspected surgical site wound infection cases were included in the study. Wound swab sample from surgical site was collected by sterile cotton swab. All the samples were immediately sent to the microbiology laboratory. Culture and sensitivity were done by standard bacteriological method. Result: Out of 133 SSIS cases, 82(51.57%) were culture positive. Out of 82 culture positive cases, 38(45.23%) were Gram positive and 46 (54.76%) were Gram negative. Predominant organisms were Esch.coli 20(23.80%) and Staphylococcus aureus 20 (23.80%). Most of the organisms were resistant to Cephalosporin group while Carbapenem, Colistin, Piperacillin Tazobactum and Amikacin showed low level of resistance. Quinolones were more effective against Gram positive than Gram negative bacteria. Methicillin resistant Staphylococcus aureus were 11 (55%). Conclusion: Esch.coli and Staphylococcus aureus were the major pathogen isolated from SSIS in our study. Cephalosporins were least effective drug. Carbapenem is the most effective drugs. For prevention of SSIS reinforcement of infection control policy for the health care worker is very important. J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 25-31